Temporal Coherence Behavior of a Nd:YAG Pumped Waveguide Raman Shifter - Cadatal, Marilou; Torres, Ma. Leilani; Garcia, Wilson (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
We study the behavior and report the control of the temporal coherence length zc of a 355/532 nm Nd:YAG pumped H2 Raman shifter with and without capillary waveguide (CWG). Depending on the application of the Raman-shifter light source, zc could be tuned rapidly or slowly by varying the H2 pressure P or the input power Pin. A more dynamic zc behavior is observed for a waveguide Raman shifter.